2017
DOI: 10.1017/s1751731117000325
|View full text |Cite
|
Sign up to set email alerts
|

Factors of importance when selecting sows as embryo donors

Abstract: The improvement in porcine embryo preservation and non-surgical embryo transfer (ET) procedures achieved in recent years represents essential progress for the practical use of ET in the pig industry. This study aimed to evaluate the effects of parity, weaning-to-estrus interval (WEI) and season on reproductive and embryonic parameters at day 6 after insemination of donor sows superovulated after weaning. The selection of donor sows was based on their reproductive history, body condition and parity. The effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…However, other factors, including parity, the weaning‐to‐oestrous interval (WEI) or the season of the year, can decisively influence donor embryo production outcomes and affect the entire ET success. Because there was hardly any information regarding the impact of these factors on embryo production and quality, we investigated whether parity (2 to 7), WEI (oestrus within 3 to 4 days) and season (fall, winter and spring) had any influence on the number of corpora lutea and ovarian cysts, number and quality of collected embryos, embryo developmental stages and recovery and fertilization rates of embryo‐producing donors (Nohalez et al., ). The results of this study showed a lack of significant effects of all variables evaluated or their interactions on any of the reproductive and embryonic parameters examined.…”
Section: Factors Affecting the Et Technologymentioning
confidence: 99%
“…However, other factors, including parity, the weaning‐to‐oestrous interval (WEI) or the season of the year, can decisively influence donor embryo production outcomes and affect the entire ET success. Because there was hardly any information regarding the impact of these factors on embryo production and quality, we investigated whether parity (2 to 7), WEI (oestrus within 3 to 4 days) and season (fall, winter and spring) had any influence on the number of corpora lutea and ovarian cysts, number and quality of collected embryos, embryo developmental stages and recovery and fertilization rates of embryo‐producing donors (Nohalez et al., ). The results of this study showed a lack of significant effects of all variables evaluated or their interactions on any of the reproductive and embryonic parameters examined.…”
Section: Factors Affecting the Et Technologymentioning
confidence: 99%
“…In this experiment, we only used weaned sows of parity 3–7 because they are readily available on farms and because they are usually preferred in ET programs ( 3 ). In addition, unlike prepubertal and mature gilts ( 24 27 ), their response to superovulation treatment is very efficient in terms of embryo production and quality ( 11 ), which makes the use of these sows as embryo donors advisable.…”
Section: Discussionmentioning
confidence: 99%
“…However, pig ET has been considered impractical for many years, primarily because of the surgical procedures required to obtain and transfer embryos, in addition to the difficulties in preserving embryos from this species. These circumstances have changed considerably in recent years, as recent advances now allow nonsurgical ET with short-(liquid state) and long-term (vitrified) preserved embryos (1)(2)(3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…All sows included in the study were weaned at interval days 21–24 post‐partum, and only those sows with a weaning to oestrus interval of 4 to 5 days were included in the experiment. Sows were selected according to an optimal reproductive history (averaging fertility >90% and litter size >10 piglets) and adequate body condition (2.7 to 3.2 on a five‐point scale on the day of weaning) following the criteria previously (Nohalez et al., 2017 ).…”
Section: Methodsmentioning
confidence: 99%